Green synthesis of 2-deoxy-D-ribonolactone from cellulose-derived levoglucosenone (LGO): A promising monomer for novel bio-based polyesters. (5th October 2021) - Diot-Néant, F.; Mouterde, L.M.M.; Couvreur, J.; Brunois, F.; Miller, S.A.; Allais, F.
Graphical abstract: Highlights: Hazardous Et3 N can be replaced by K3 PO4 for the hydration of levoglucosenone (LGO). LCA shows that K3 PO4 -catalyzed hydration of LGO is greener than the Et3 N-based one. Hydrated LGO is oxidized into 2-deoxy-D-ribonolactone via Baeyer-Villiger oxidation. 2-deoxy-D-ribonolactone is a promising monomer for the production of polyesters. These LGO-based polyesters are potential substitutes to fossil fuel-based polymers. Abstract: The already reported, yet hazardous, Et3 N-catalyzed levoglucosenone (LGO ) hydration into 1, 6-anhydro-3-deoxy-β - D- erythro -hexo-pyranose-2-ulose (LGO-OH ) has been greened up by substituting Et3 N with K3 PO4 and performing the reaction in H2 O. Optimal reaction conditions (K3 PO4 (0.05 eq.), [LGO ] = 0.08 M, 5 h) not only allowed higher yields, but also limited the homocoupling of LGO, a competitive side reaction. A comparative – yet non-comprehensive and perfectible – Life Cycle Assessment (LCA) using the CML 2002 method highlighted the specific impacts where this revisited synthesis outperformed the Et3 N-catalyzed one. 1, 6-Anhydro-3-deoxy-β-D- erythro -hexo-pyranose-2-ulose was then subjected to a one-pot catalyst- and organic solvent-free Baeyer-Villiger oxidation/rearrangement, without the need to perform acidic hydrolysis, to access 2-deoxy-D-ribonolactone (HO-HBO, 79% yield). To assess the potential of HO-HBO as monomer for the production of novel bio-based polyesters, the latter was finally polymerized in the presence of aliphatic diacyl chlorides to make a proof-of-concept. Resulting polyesters exhibited promising glass transition temperature ( T g ) values between −21 and −2 °C and melting temperatures ( Tm ) from 87 to 144 °C, demonstrating the potential of HO-HBO for the production of sustainable alternatives to current fossil fuel-based polymers.